The Effect of Learning Basic Volleyball Passing Techniques Using The Playing Method on Physical Education Learning Outcomes - Azi Alam Sudrajat; Rizal, Bayu Thomi (Universitas PGRI Palembang, 2025)
This study aims to determine the effect of learning basic volleyball passing techniques using the playing method on physical education learning outcomes in grade IV students at SDN Dukuh 08 Pag. Learning basic passing techniques with the play method is an active approach that involves students in game activities that are fun, directed, and in accordance with motor development. This method not only focuses on mastering movement techniques, but also fosters motivation, cooperation, and coordination of students' movements. The learning outcomes of physical education in this study include cognitive, affective, and psychomotor domains, especially in volleyball upper and lower passing skills. This study uses a quantitative approach with quasi-experimental methods and posttest-only control group design. The research sample consisted of 60 grade IV students who were divided into two groups: the experimental class that received learning using the play method, and the control class that received conventional learning. The data collection instrument used an observation sheet consisting of 6 aspects and 18 indicators of upper and lower passing techniques, with an assessment scale of 1–5. The validity of the instrument was consulted with a physical education expert, but the reliability was not tested. Data analysis was carried out using normality tests, homogeneity tests, independent sample t-tests, and effect size calculations with the help of IBM SPSS Statistics 27 software. The results showed that the data was normally distributed (Sig. > 0.05), but not homogeneous (Sig. < 0.05). The t-test showed a significant difference between the experimental and control classes in the upper passing (t = 13.675) and lower passing (t = 11.500) results. The calculation of effect size shows a very high influence. Thus, learning basic volleyball passing techniques through the playing method has been proven to have a significant effect on students' physical education learning outcomes